TOXICIDADE E POTENCIAL ANTIOXIDANTE DAS FOLHAS E CASCAS DE Ocotea puberula (RICH.) NEES (LAURACEAE) - SILVA, Cristiane Aparecida Rosa Pavera; ADRIANO, Bruno Braga Nogueira; CRUZ, Sorraylla Layanny Alvarenga; SILVA, Ana Francisca Gomes; BATISTA-SILVA, Valéria Flávia (ANAIS DO ENIC, 2022)
-